2018
DOI: 10.3390/ijms19113587
|View full text |Cite
|
Sign up to set email alerts
|

Polygonatum odoratum Polysaccharides Modulate Gut Microbiota and Mitigate Experimentally Induced Obesity in Rats

Abstract: Increasing evidence suggests that the gut microbiota plays vital roles in metabolic diseases. Polygonatum odoratum extract alleviates hyperglycemia and hyperlipidemia, but the underlying mechanism remains unclear. This study investigated the effects of P. odoratum polysaccharides (POPs) on high-fat diet (HFD)-induced obesity in rats and whether these effects were related to modulation of gut microbiota. POP treatment attenuated weight gain, fat accumulation, epididymal adipocyte size, liver triglycerides, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 63 publications
4
53
0
Order By: Relevance
“…Propionic acid has a positive effect on cholesterol metabolism. Interestingly, the trend was the same as the changes in TC and TG levels [34,35,36]. In addition, HLP-H displayed a distinct increase in the release of isobutyric acid (approximately 0.09 mmol/L) in the fourth week ( p < 0.05).…”
Section: Resultsmentioning
confidence: 64%
“…Propionic acid has a positive effect on cholesterol metabolism. Interestingly, the trend was the same as the changes in TC and TG levels [34,35,36]. In addition, HLP-H displayed a distinct increase in the release of isobutyric acid (approximately 0.09 mmol/L) in the fourth week ( p < 0.05).…”
Section: Resultsmentioning
confidence: 64%
“…9B, C, D, and E). It has been reported that HFD contributed to the reduction of relative abundances of bacteroidaceae (47), bifidobacteria, and lactobacillus colonies (48), which could weaken the process of cholesterol conversion and utilization, leading to hyperlipidemia (49)(50)(51). Lactobacillus was proved to inhibit HFD-induced obesity by down-regulating PPARγ and C/EBPα (52).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is likely that the reduction of H 2 S-producing bacteria by pistachio enhances the output of short chain fatty acids (SCFAs), such as butyrate, improving intestinal health and inflammation [76]. Coprobacillus has been reported to be negatively correlated with most of the features of obesity in obese rats [77,78]. An abundance of Oscillospira has been associated with systemic inflammation and altered intestinal permeability [79,80] and diets rich in polyphenols improve HFD-induced liver steatosis by reducing Oscillospira abundance [81,82].…”
Section: Discussionmentioning
confidence: 99%